The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/826303
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Host Defense against Staphylococcal Infections

Abstract: Preterm infants are especially susceptible to late-onset sepsis that is often due to Gram-positive bacterial infections resulting in substantial morbidity and mortality. Herein, we will describe neonatal innate immunity to Staphylococcus spp. comparing differences between preterm and full-term newborns with adults. Newborn innate immunity is distinct demonstrating diminished skin integrity, impaired Th1-polarizing responses, low complement levels, and diminished expression of plasma antimicrobial proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 105 publications
1
21
0
3
Order By: Relevance
“…Toxins may contribute to MRSA persistence in the host, relapse of infections, tissue damage, and the production of proinflammatory cytokines [47, 51, 52]. The neonatal immune response to MRSA has not been elucidated so far [53]. Some data suggest that neonates are prone to developing hyperinflammation during staphylococcal infections [54, 55].…”
Section: Toxinsmentioning
confidence: 99%
“…Toxins may contribute to MRSA persistence in the host, relapse of infections, tissue damage, and the production of proinflammatory cytokines [47, 51, 52]. The neonatal immune response to MRSA has not been elucidated so far [53]. Some data suggest that neonates are prone to developing hyperinflammation during staphylococcal infections [54, 55].…”
Section: Toxinsmentioning
confidence: 99%
“…Coagulasenegative staphylococci such as S. epidermidis are the most common causes of bacteremia in preterm infants, especially those of low gestational age [12,13]. Staphylococcus epidermidis is a ubiquitous skin commensal responsible for approximately 50% of all cases of late-onset neonatal septicemia [14].…”
mentioning
confidence: 99%
“…A study of human neonates showed impaired Th1 polarization in response to infection by Staphylococcus species [27], thought to result from programming by the maternal immune system in utero as a safeguard against catastrophic immune reactions, specifically by means of increased prevalence of Treg [28]. Maternal antibodies transferred through the placenta or in milk also interfere with effective vaccination, as these circulating antibodies can reduce the availability of antigen to the neonate’s own immune cells [17], and the neonatal Fc receptor increases the serum half-life of passively transferred antibodies [29].…”
Section: Neonatal Immunitymentioning
confidence: 99%